1981
DOI: 10.1128/jvi.38.3.996-1004.1981
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Epstein-Barr virus nuclear antigen by fluoroimmunoelectrophoresis and radioimmunoelectrophoresis

Abstract: A 65,000-dalton (65K) antigen found in Raji cells by fluoroimmunoelectrophoresis and radioimmunoelectrophoresis has been identified as an Epstein-Barr virus nuclear antigen (EBNA). This identification is based on the following evidence. The 65K antigen is detected in Raji cells but not in three Epstein-Barr virus (-) human B cell lines. It is not detected with EBNA (-) sera. The 65K antigen is found predominantly in the nucleus and co-elutes with EBNA during partial purification by DNA-Sepharose and Blue Dextr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…In contrast, we found sera which were negative both for EBNA-2 in ACIF and for 86 kd on immunoblots. Our finding that both EBNA-1 and 86 kd are dsDNA-binding is in agreement with the findings of Strnad et al, (1981). and the presence of both EBNA-1 and 86 kd in the nuclear fractions of cells confirms the results of Hennessy and Kieff (1983).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, we found sera which were negative both for EBNA-2 in ACIF and for 86 kd on immunoblots. Our finding that both EBNA-1 and 86 kd are dsDNA-binding is in agreement with the findings of Strnad et al, (1981). and the presence of both EBNA-1 and 86 kd in the nuclear fractions of cells confirms the results of Hennessy and Kieff (1983).…”
Section: Discussionsupporting
confidence: 93%
“…A recent study has identified an 82 kd polypeptide present in the nuclear fraction of EBV-carrying cell lines, but not in EBV-negative lines (Hennessy and Kieff, 1983). Previously, Strnad et al, (1981) who first detected EBNA-1 on immunoblots also observed an 81 kd polypeptide detected in 2/4 EBV-positive cell lines by 2/5 EBV-positive antisera. It was suggested that this polypeptide might be EBV-specific.…”
mentioning
confidence: 88%
“…In contrast, only 10 of 27 Burkitt lymphoma lines expressed EBNA-2. Four of the lines were EBNA-2negative when analyzed by immunoblotting (Dambaugh et al, 1984;Dillner et al, 1985a,b;Strnad et al, 1981). Two of these (Daudi and P3HR-1) release or can be induced to release non-transforming virus with a completely deleted EBNA-2 region.…”
Section: Restriction Enzyme Analysis Of the Lt-i Regionmentioning
confidence: 99%
“…Antibodies to one of the 3 possible reading frames in the third internal repeat array in LT-2 conclusively identified the LT-2 gene product as a 70-92-kDa nuclear polypeptide, designated EBNA-1 (Dillner et al, 1984;Heller et al, 1981). Recently, several reports have described a second EBV-associated nuclear antigen, EBNA-2, detected by sera from EBV-seropositive donors by immunoblotting (Dillner et al, 19856;Hennessy and Kieff, 1983;Sculley et al, 1984;Strnad et al, 1981) and by immunofluorescence (Dillner et al,198%). This has also been shown by the production of antisera to a bacterial fusion protein containing part of the LT-1 region (Hennessy and Kieff, 1985).…”
mentioning
confidence: 99%
“…A primary infection is confirmed serologically by the initial detection of antibody to the EBV-specific viral capsid antigen (VCA) followed by the later appearance (usually after 1-6 mo) of antibodies to the EBV encoded nuclear antigen (EBNA) (2); for a review, see de The (3) and Henle and Henle (4). EBNA-I , the first nuclear antigen to be recognized, has been identified as a 69,000-85,000 protein by the immunoblotting technique (5)(6)(7). The size of the EBNA-I protein is correlated with the variation of the length of the IR-3 region of EBV-DNA (6).…”
Section: Introductionmentioning
confidence: 99%